Study of the water quality of Alqueva reservoir in the south of Portugal using MERIS data - Potes, Miguel (2012)
The successful launch of ENVISAT (ENVIronmental SATellite) in March 2002 has given a great opportunity to understand the changes of water color using high spatial resolution data. In this study, the potential of MERIS (Medium Resolution Imaging Spectrometer) sensor to describe variations of optically active substances of Alqueva reservoir is investigated. Regular laboratory analyses, from 2003 to 2006, are used in combination with MERIS acquisitions. The surface reflectance is derived from Level 1b MERIS data, using radiative transfer calculations to account for the atmospheric effects. The empirical algorithms obtained are used to map chlorophyll a and cyanobacteria. The results obtained are also compared with independent laboratory measurements taken during year 2007.